Normalhistologi hos oppdrettet rognkjeks (Cyclopterus lumpus L.). Med fokus på organene hud, gjeller, hjerte, nyre, milt, pankreas og lever - Klingenberg, Oda (UiT The Arctic University of Norway, 2019)
Lumpfish (Cylcopterus lumpus) is increasingly used as cleaner fish in intensive farming of Atlantic salmon (Salmo salar) with an aim to control the infection of lice on the salmon. The lumpfish is itself exposed to a number of infections, both bacterial, viral, parasitic and fungal, and there is still a lack of knowledge regarding these infections and their impact on the fish. In order to assess the importance of infections on a host and in different types of tissues, a detailed knowledge of the normal histology is crucial. One of the aims of the FHF-project “Parasitic infection in Lumpfish: Nucleospora cyclopteri” (project number 901320) is to describe the normal histology of the lumpfish, and this MSc thesis contributes to that aim. 50 clinically healthy Lumpfish sized <5g-132g (fry to juvenile stages) were euthanized, and samples from skin, gills, heart, kidney, spleen, pancreas and liver were fixated in formalin (>48h). The organ samples were embedded in paraffine wax and sectioned in 5m sizes. Histological sections were made, and stained in Hematoxylin (Gill, Mayer and a variant of Harris) and Eosin (Y and G). In addition, different special dyes were used. AB-PAS staining was used in samples from skin, gills and pyloric caeca, MGG in head kidney and spleen and VG in skin and pancreatic tissue. Histological sections were analyzed using light microscope directly or on the computer after digital scanning of the stained sections. Results from the HE stains shows differences in lumpsucker skin, gills, heart ventricle and liver compared to Atlantic salmon. Lumpfish skin, liver and atrium shares similarities with cod (Gadus morhua). Results from special staining with AB-PAS shows numerous gill and pyloric caeca mucus cells, and some mucus cells in the lumpsucker skin. Vacuoles in lumpsucker skin did not take up any staining with AB-PAS. More research on the normal histology of organs in the lumpsucker is needed, but this thesis gives an introduction to the normal histology of several of the commonly used ...